1983
DOI: 10.1159/000465324
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of the Term ‘Posttransfusion Hepatitis Type B’ in Its Conventional Sense Still Justifiable?

Abstract: We have investigated 8 cases of clinically manifest hepatitis type B said to be posttransfusion hepatitis that have become known in the years 1978-1981. Paired samples of serum from all 54 blood donors implicated have been drawn at the time of the donation in question as well as a few months later. Only 1 donor, negative for HBsAg but positive with high titer for anti-HBc, could have been a possible source of infection. There is strong evidence that this person is a chronic low level carrier. In the case of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…The few cases of posttransfusion hepatitis type B (0.4%) could be attributed to the existence of donors with serum levels of HBsAg below the sensitivity of the assay (19), although some cases of hepatitis B could also be due to intrahospital transmission of hepatitis B virus (20). At variance with other studies (21), we found only one patient with CMV-related posttransfusion hepatitis.…”
Section: Discussioncontrasting
confidence: 65%
“…The few cases of posttransfusion hepatitis type B (0.4%) could be attributed to the existence of donors with serum levels of HBsAg below the sensitivity of the assay (19), although some cases of hepatitis B could also be due to intrahospital transmission of hepatitis B virus (20). At variance with other studies (21), we found only one patient with CMV-related posttransfusion hepatitis.…”
Section: Discussioncontrasting
confidence: 65%